2019
DOI: 10.11113/mjfas.v15n2-1.1542
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, antioxidant and phytochemical screening of propolis extracts from four different Malaysian stingless bee species

Abstract: Propolis is a plant-derived substance collected by stingless bee’s product from various sources, including plant resins with combination of bee’s saliva and wax. Propolis has been used to treat several diseases since ancient times and it is an important source of bioactive natural compound and drug derivatives. The aim of this study was to evaluate biological and chemical profiles of ethanolic extracts from propolis produced by Heterotrigona itama (HI), Geniotrigona thoracica (GT), Lepidotrigona terminate (LT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The previous cytotoxicity study on EEP of T. apicalis by Mat Nafi et al [ 9 ] reported that EEP did not exhibit cytotoxic activity against different cancer cell lines. MDA-MB-231, SK-UT-1, and HeLa for 72 hours with IC 50 of HeLa were 68 μ g/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous cytotoxicity study on EEP of T. apicalis by Mat Nafi et al [ 9 ] reported that EEP did not exhibit cytotoxic activity against different cancer cell lines. MDA-MB-231, SK-UT-1, and HeLa for 72 hours with IC 50 of HeLa were 68 μ g/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Each well was added with 100 μ L DMSO. The purple colour formed due to the dissolved formazan with DMSO corresponded to the number of viable cells [ 9 ]. The absorbance was measured at 570 nm with a spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DPPH free radical scavenging activity of propolis extracts was determined according to the technique by Nafi et al (2019). Quercetin served as the standard reference.…”
Section: 2-diphenyl-1-picrylhydrazyl (Dpph) Free Radical Scavenging A...mentioning
confidence: 99%